2018
DOI: 10.3389/fonc.2018.00402
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in Total and Site-Specific Cancer Incidence in Germany: A Population-Based Registry Study

Abstract: Most chronic diseases follow a socioeconomic gradient with higher rates in lower socioeconomic groups. A growing body of research, however, reveals cancer to be a disease group with very diverse socioeconomic patterning, even demonstrating reverse socioeconomic gradients for certain cancers. To investigate this matter at the German national level for the first time, this study examined socioeconomic inequalities in cancer incidence in Germany, both for all cancers combined as well as for common site-specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
2
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(130 citation statements)
references
References 79 publications
8
96
2
10
Order By: Relevance
“…19 The most studied individual-level SES indicator is education, for which overall RR estimates in men range from 1.5 to 3 and are generally even higher than those found for lung cancer. Effect of area deprivation in men in France 16,17,37 , Germany 18,19 , Spain 38 and Italy 29 was found to be between 1.5 and 2.0, whereas in a Scottish study cancers of the mouth, oropharynx and larynx were each shown to be twice to over 3-times as likely in people from the most deprived compared to the least deprived ar-eas, though they did not stratify by sex. 39 There is convincing evidence that area deprivation has an independent effect on UADT cancer risk, not explained by individual factors.…”
Section: Cancers Of the Upper Aerodigestive Tract And Stomach Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…19 The most studied individual-level SES indicator is education, for which overall RR estimates in men range from 1.5 to 3 and are generally even higher than those found for lung cancer. Effect of area deprivation in men in France 16,17,37 , Germany 18,19 , Spain 38 and Italy 29 was found to be between 1.5 and 2.0, whereas in a Scottish study cancers of the mouth, oropharynx and larynx were each shown to be twice to over 3-times as likely in people from the most deprived compared to the least deprived ar-eas, though they did not stratify by sex. 39 There is convincing evidence that area deprivation has an independent effect on UADT cancer risk, not explained by individual factors.…”
Section: Cancers Of the Upper Aerodigestive Tract And Stomach Cancermentioning
confidence: 99%
“…13,15,29 Studies relying on area-level SES as a proxy for individual SES (Supplementary table 3) provided RR estimates in the same range. [16][17][18][19][20][21][22] Different individual and area factors when mutually adjusted or unadjusted exhibit comparable strength of association. Aside from unemployment, for which observed RRs were occasionally found to exceed 4 13 (a finding which could result also from reverse causality or significant comorbidity that was not adjusted for), generally, point estimates do not exceed RR of 2.…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have also provided evidence that the magnitude of the cancer burden is negatively associated with socioeconomic status [16,[31][32][33][34]. Furthermore, adverse health outcomes (e.g., worse health status, long and short-term disability and shorter life expectancy) were disproportionately found in poorer people as opposed to those with higher socio-economic status [13,16,31,33,[64][65][66][67][68][69][70][71]. Contribtuing factors to the high rates of long term health impacts among the poorest groups includes higher tobacco rates [16,27], economic burden [35,36], increased mental illness [72], lack of health education and awareness [73], and less access to competent and effective health care services [73].…”
Section: Discussionmentioning
confidence: 99%
“…Für viele dieser Erkrankungen ist auch für die in Deutschland lebende Bevölkerung nachgewiesen, dass sie in niedrigen sozioökonomischen Statusgruppen häufiger vorkommen als in statushöheren Gruppen, z. B. für die koronare Herzkrankheit [35], den Diabetes mellitus [36], die chronische Bronchitis [37] und bei Männern auch für den Lungenkrebs [38]. Als weitere Risikofaktoren für schwere Verläufe von COVID-19 wurden bisher das Zigarettenrauchen [39] und das starke Übergewicht [40] diskutiert.…”
Section: Soziale Ungleichheit Und Covid-19-risikofaktorenunclassified